ANALISISBEBAN KERJA FISIK DAN MENTAL SERTA STRES KERJA PERAWAT SECARA ERGONOMICS PADA RUMAH SAKIT JIWA TAMPAN PEKANBARU - Suhermiati '; Samsir '; Iwan Nauli Daulay (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2015)
Nurse is a profession that risky from stress. Conditions of workload and job stress note to be know determined needs quality and quantity of nurses needed, to prevent workloads that do not fit or are not comparable with the ability of the nurses had. The workload consists of a physical and mental workload. The study aims to determine the llevel of physical and mental workload and stress of nurses working in psychiatric hospitals ergonomics Pekanbaru Tampan. Physical workload measured by caloric needs and mental workload measured by subjective methods (SWAT). This type is descriptive research. Samples were taken by purposive sampling. Based on the research of the respondent’s characteristics, it is found out that 26,92% of nurses are 34-39 aged, 51,92% of nurses are female, 50-63kg of nurses are 55,77% weight. Levels of physical workload that the mild, namely mental workload levels in the medium category and levels of work stress in the mild category.Keywords: Workload, stress, nurse,ergonomics, and psychiatric hospitals